Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am trying to understand the solution of a problem.

$X_1,X_2,....$ a sequence of independents randoms variables and same probability distribution.

$N$ rv. taking its values in $\mathbf{N}$

Considering $Z=\sum_{i=i}^N X_i$

We have : $$G_Z(s)=E(s^Z)=E(s^{\sum_{i=0}^N X_i})=\sum_kE(s^{\sum_{i=0}^N X_i}|N=k)P(N=k) $$

I don't understand how can we pass from $E(s^{\sum_{i=0}^N X_i})$ to that $\sum_kE(s^{\sum_{i=0}^N X_i}|N=k)P(N=k)$

share|cite|improve this question

1 Answer 1

up vote 0 down vote accepted

For every measurable partition $(A_n)_{n\geqslant0}$ of the space $\Omega$ such that $\mathrm P(A_n)\ne0$ for every $n\geqslant0$, and every integrable random variable $Y$, $$ \mathrm E(Y)=\sum_{n=0}^{+\infty}\mathrm E(Y:A_n)=\sum_{n=0}^{+\infty}\mathrm E(Y\mid A_n)\cdot\mathrm P(A_n). $$ Apply this to $Y=s^Z$ and $A_n=[N=n]$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.